If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 28 = 14x + -60 Reorder the terms: 28 + 6x = 14x + -60 Reorder the terms: 28 + 6x = -60 + 14x Solving 28 + 6x = -60 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 28 + 6x + -14x = -60 + 14x + -14x Combine like terms: 6x + -14x = -8x 28 + -8x = -60 + 14x + -14x Combine like terms: 14x + -14x = 0 28 + -8x = -60 + 0 28 + -8x = -60 Add '-28' to each side of the equation. 28 + -28 + -8x = -60 + -28 Combine like terms: 28 + -28 = 0 0 + -8x = -60 + -28 -8x = -60 + -28 Combine like terms: -60 + -28 = -88 -8x = -88 Divide each side by '-8'. x = 11 Simplifying x = 11
| 5(2t-5)= | | 30=-8v+6(v+6) | | 2y+3y-4y+5y= | | 10x+3[5+6(x+2)]=-5 | | 3x+27=13x-83 | | m-8m+4m+1= | | 2x+7=x+21 | | 8-3(-12x+2)= | | 7[9-7(8-z)]-9=9[7(9z-8)+6]-82 | | m+5m-7m+4= | | 8n-3=43 | | 5x+241=14x-11 | | 49-6x=3x+16 | | (x)(7)-12=23 | | 9-9x=35-23x | | 60-7x=25x+20 | | -10(8w+7)-4(6w+3)= | | 4y-9y=-2 | | 9x-x=-16 | | 64-6x=3x+17 | | 5n+3G-n+5=26 | | 7[9-7(8-q)]-9=9[7(9q-8)+6]-82 | | 3y-7y=-19+11 | | 13-9x=37-16x | | -2x+(-7x)=81 | | 7-8x=25-22x | | 56-3x=6x+16 | | -73-7x=9x+23 | | 4+17=4y-y | | 9x+6x=21 | | 3(5-5)=-6(-2+2) | | 5w+3w= |